2016
DOI: 10.7860/jcdr/2016/19399.7860
|View full text |Cite
|
Sign up to set email alerts
|

Malposition of Subclavian Venous Catheter Leading to Chest Complications

Abstract: Although Central Venous Catheter (CVC) placement is a relatively simple procedure but its insertion and maintenance are associated with significant risks. Malposition (defined as any CVC tip position outside the superior vena cava) may be associated with catheter insertion and may require immediate intervention. It may result in complications like haemothorax, pleural effusions, pneumothorax, sepsis, thrombosis and cardiac tamponade. This case report presents timely detection of the complication after placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…8 Leang et al and Kumar et al reported misplaced catheter in the pleural space. 9,10 Author could not find any case report of mediastinal placement of feeding tube through basilic vein.…”
Section: Discussionmentioning
confidence: 98%
“…8 Leang et al and Kumar et al reported misplaced catheter in the pleural space. 9,10 Author could not find any case report of mediastinal placement of feeding tube through basilic vein.…”
Section: Discussionmentioning
confidence: 98%
“…Previous case studies have described the misplacement of central venous catheters or hemodialysis catheter into the azygous vein [8], accessory hemiazygous vein [9], brachiocephalic vein, subclavian vein [10], brachiocephalic artery [11], mediastinum [12], pleural space [13], left atrium [14] and pericardium [15].…”
Section: Introductionmentioning
confidence: 99%
“…, 3 Other complications include hydrothorax, hemothorax, chylothorax, extravasation of infusate, cardiac tamponade, mediastinal hemorrhage, and malpositioning of the catheter 13 Catheter malpositioning can cause malfunction and can also lead to other complications, like jugular or subclavian retrograde infusion and the other complications mentioned above, e.g. mediastinal or pleural bleeding.…”
Section: Introductionmentioning
confidence: 99%